2022
DOI: 10.3390/pathogens11060631
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Year Look at the Phylogenetic Profile, Antimicrobial Resistance, and Associated Virulence Genes of Uropathogenic Escherichia coli

Abstract: Uropathogenic Escherichia coli is the most common cause of urinary tract infections, resulting in about 150 million reported annual cases. With multidrug resistance on the rise and the need for global and region surveillance, this investigation looks at the UPEC isolates collected for a 3-year period, with a view of ascertaining their antimicrobial susceptibility patterns and associated virulence determinants. The identification of bacteria isolates, antimicrobial susceptibility, and extended-spectrum beta-lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…Similarly, the highest co-existence of the gene bla CTX-M+TEM (21%) was found in the ESBL E. coli & K. pneumoniae from Qatar [59], Saudi Arabia [45, 69] and followed by the least co-existence of the genes bla TEM+SHV, bla CTX-M+SHV & bla CTX-M+TEM+SHV were detected in their same studies, but in contrast, the Moglad et al , Badger-Emeka et al and Sid Ahmed et al found that the highest co-harbored genes were bla CTX-M+TEM+SHV (50% & 24.7%), bla CTX-M+SHV (50% & 10.1%) found in the E. coli , K. pneumoniae and other Enterobacterales in their studies. [70,71] Likewise, the lowest co-expression of the genes bla TEM+NDM , bla TEM+IMP and bla CTX-M+TEM+SHV+IMP were also detected in 2.22% K. pneumoniae, 5% P. aeruginosa and 10% of each A. baumannii to each gene combination. In such a way, Elbadawi HS e t al.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the highest co-existence of the gene bla CTX-M+TEM (21%) was found in the ESBL E. coli & K. pneumoniae from Qatar [59], Saudi Arabia [45, 69] and followed by the least co-existence of the genes bla TEM+SHV, bla CTX-M+SHV & bla CTX-M+TEM+SHV were detected in their same studies, but in contrast, the Moglad et al , Badger-Emeka et al and Sid Ahmed et al found that the highest co-harbored genes were bla CTX-M+TEM+SHV (50% & 24.7%), bla CTX-M+SHV (50% & 10.1%) found in the E. coli , K. pneumoniae and other Enterobacterales in their studies. [70,71] Likewise, the lowest co-expression of the genes bla TEM+NDM , bla TEM+IMP and bla CTX-M+TEM+SHV+IMP were also detected in 2.22% K. pneumoniae, 5% P. aeruginosa and 10% of each A. baumannii to each gene combination. In such a way, Elbadawi HS e t al.…”
Section: Discussionmentioning
confidence: 99%
“…While the percentage of isolation of Escherichia coli in the current study was not consistent with the results obtained by the researcher (18) and it may be the cause of urinary tract infections in children under the age of two, as this indicates the presence of congenital defects in the urinary system or kidneys (19) . which reached the percentage of isolation from children and both sexes (64%), from females (80%) and from males (20) . The results of the current study were inconsistent with the results of the researcher (20) as the percentage of the presence of the papE gene was (14%).…”
Section: Molecular Diagnosis Of E Coli Using the Pape Genementioning
confidence: 89%
“…which reached the percentage of isolation from children and both sexes (64%), from females (80%) and from males (20) . The results of the current study were inconsistent with the results of the researcher (20) as the percentage of the presence of the papE gene was (14%). The results reached by (18) the percentage of the presence of the papE gene (37.5%), ie 15 isolates out of a total of 40 isolates.…”
Section: Molecular Diagnosis Of E Coli Using the Pape Genementioning
confidence: 89%
“…Twenty-four Saudi studies were identified in the literature that evaluated the susceptibility of members of Enterobacterales to β-lactam antimicrobials, particularly extended-spectrum cephalosporins [ 28 , 29 , 33 , 39 , 47 , 52 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. Seventeen studies provided detailed antimicrobial susceptibility results for each tested organism [ 28 , 33 , 52 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. Eight studies evaluated urine samples, whereas the rest of the studies assessed samples from different sites [ 33 , 52 , 55 , 58 , 61 ...…”
Section: Resistant Gram-negative Pathogensmentioning
confidence: 99%